DIGITAL COMMUNITY MARKETING COMMUNICATION ON PLATFORM X: A STUDY CASE ON MURAH-MURAH COMMUNITY MARKETING - Saepudin Saepudin; Nasywa Fadya (PT Altin Riset Publishing, 2026)
The nature of interactions in the context of digital communication, or social media, is characterized by its increasing complexity, resulting from the ability to engage numerous individuals simultaneously in a virtual environment. In this context, online communities have emerged as a compelling arena for the study of social dynamics, including the dynamics of digital community-based communication. This study analyses the digital community marketing strategies employed by Murah-Murah in order to build and maintain a loyal member base. The present study is predicated on four fundamental pillars: The factors to be considered include consumer trust, brand awareness, engagement with consumers, and long-term relationships. The study determined that Consumer Trust constitutes a fundamental basis, predicated upon the transparency of interactions and the administrator's proactive protection mechanism, thereby engendering a trustworthy environment conducive to buying and selling. The Murah-Murah X Community has demonstrated a robust brand awareness, exhibiting a substantial and accelerating growth trajectory. This growth is primarily driven by the community's core values of saving and sharing, which have been a primary catalyst for its widespread recognition. Engagement with consumers is effective through attractive and honest product presentation, unique item offerings, easy and secure shopping processes, and because it is directed towards trusted e-commerce platform transactions. The strategic implementation of these pillars is instrumental in fostering long-term relationships, with the objective of transitioning new customers into a state of brand loyalty and becoming advocates within their respective communities. In summary, the Murah-Murah community on platform X has effectively solidified its standing as a preeminent digital marketplace through a distinctive integration of communication, transparency, proactive security measures, a consumer-centric approach, and the cultivation of enduring relationships.